New Coumarin-Thiosemicarbazone Based Zn(II), Ni(II) and Co(II) Metal Complexes: Investigation of Cholinesterase, ?-Amylase, and ?-Glucosidase Enzyme Activities, and Molecular Docking Studies - Celik, Esra; Ozdemir, Mucahit; Koksoy, Baybars; Taskin-Tok, Tugba; Taslimi, Parham; Sadeghian, Nastaran; Yalcin, Bahattin (Wiley-V C H Verlag Gmbh, 2023)
New coumarin-thiosemicarbazone compounds and their zinc(II), nickel(II), and copper(II) metal complexes were synthesized and characterized. The inhibitory activities of these new coumarin-thiosemicarbazone-based metal complexes against butyrylcholinesterase (BChE), acetylcholinesterase (AChE), alpha-amylase, and alpha-glucosidase were determined. The results showed that all the synthetic compounds exhibited potent inhibitory activities against all targets, as compared to the standard inhibitors, as revealed by the half-maximal inhibitory concentration (IC50) and the inhibitory constant (Ki) values. The Ki values of the new complexes for BChE, AChE, and alpha-glucosidase enzymes were obtained in the ranges of 115.84-276.07, 31.68-117.08, and 22.56-47.82 mu M, respectively. Moreover, molecular docking studies provided support for the conclusion that coumarin-thiosemicarbazone zinc(II) (-102.34; -10.41 kcal/mol) and coumarin-thiosemicarbazone cobalt(II) complexes (-25.46; -9.49 kcal/mol) act as dual inhibitors for both AChE and alpha-amylase species. Furthermore, coumarin-thiosemicarbazone cobalt(II) (-39.46 kcal/mol) and coumarin-thiosemicarbazone nickel(II) complexes (-39.41 kcal/mol) demonstrated potential as inhibitors of alpha-glucosidase. Of all the compounds studied, bis-3-benzyl-7,8-dimethoxycoumarin-thiosemicarbazonato zinc(II) is the most potent drug against AChE. New coumarin-thiosemicarbazone compound and their zinc (II) 2 a, nickel (II) 2 b, and copper (II) 2 c metal complexes were synthesized and characterized then these complexes were determined for some metabolic enzyme inhibitory activities. The Ki values of the new complexes for BChE, AChE, and alpha-glucosidase enzymes were obtained in the ranges of 115.84-276.07, 31.68-117.08, and 22.56-47.82 mu M, respectively. Of all the compounds studied, bis-3-benzyl-7,8-dimethoxycoumarin-thiosemicarbazonato zinc(II) is the most potent drug against AChE.image
Keywords: Acetylcholinesterase; Alpha-Amylase; Alpha-Glucosidase; Butyrylcholinesterase; Coumarin-Thiosemicarbazide